Changes in cloudiness over the Amazon rainforests during the last two decades: diagnostic and potential causes (2011)
ABSTRACT: This study shows a decrease of seasonal mean convection, cloudiness and an increase of surface shortwave down-welling radiation during 1984–2007 over the Amazon rainforests based on the analysis of satelliteretrieved clouds and surface radiative flux data. These changes are consistent with an increase in surface temperature, increased atmospheric stability, and reduction of moisture transport to the Amazon based on in situ surface and upper air meteorological data and reanalysis data. These changes appear to link to the expansion of the western Pacific warm pool during the December–February season, to the positive phase of the Atlantic Multidecadal Oscillation and increase of SST over the eastern Pacific SST during the March–May season, and to an increase of the tropical Atlantic meridional SST gradient and an expansion of the western Pacific warm pool during September–November season. The resultant increase of surface solar radiation during all but the dry season in the Amazon could contribute to the observed increases in rainforest growth during recent decades.